Impulse ! : work from Houston area teens. - Contemporary Arts Museum, Houston (Houston : Contemporary Arts Museum Houston, 2007)
Adams, Jessica ; Anderson, Dakota ; Ayres, Katie ; Barnes, Corrin ; Berg, Jodie ; Burnham, Patrick ; Delgado, Crystal ; Dinh, Thien ; Eng, Jon ; Holman, Sarah ; Kanan, Zoe ; LaFrate, Kristin ; Moody, Brendan ; Reiland, Jennifer May ; Rife, Kris ; Rosen, Samara ; Rosenberger, Darcy ; Ruiz, Eric ; Smith, Cameron ; Solis, Adelina ; Stokes, Kayla ; Tamez, Humberto ; Weitkunat, Sydney ; Williams, Georgia ; Wistuba, Francisca
Engels
Exhibition "Impulse ! : Work from Houston Area teens", the 156th exhibition in the Contemporary Arts Museum Houston's Perspectives series, organized by the Teen Council of the Contemporary Arts Museum Houston, 04.05.2007 - 15.07.2007
boek